Radiological assessment of the quality of root canal fillings in teeth endodontically treated at students' practical sessions - Kulić Ljiljana; Nogo-Živanović Dajana; Krunić Jelena; Vujašković Mirjana; Stojanović Nikola (Serbian Medical Society - Dental Section, Belgrade, 2011)
Introduction. The main goal of obturation is prevention of reinfection of the root canal system and consequently appearance of periapical lesion. Epidemiological studies have confirmed high prevalence of periapical lesions in endodontically treated teeth with inadequate root canal fillings. The aim of this study was to assess the quality of root canal fillings in teeth treated at students' practical sessions. Iatrogenic errors during endodontic interventions were also assessed. Methods. Two hundred dental records of the patients treated by students in the study program Dentistry at the School of Medicine in Foca during the academic year 2010/2011 were randomly chosen. The length and homogeneity of the fillings or the presence of iatrogenic errors were recorded. A root canal filling was considered adequate if it had correct length and homogeneity in the absence of iatrogenic errors. Two students' curricula V1 and V2 were evaluated for the treatment outcome. Results. Out of 128 endodontically treated teeth, adequate length of the canal filling to the physiological apex was observed in 57% of teeth, homogeneity in 78.9%, while both of these criteria were satisfied in 66 teeth (51.6%). Better quality of root canal fillings was achieved by students of the study curricula V2 and the difference between these two programs was significant (p<0.05). Better quality of root canal fillings in both study programs was recorded for incisors and canines as compared to premolars. Conclusion. The quality of endodontic treatment performed by students was considered adequate in 51.6% of cases. The type of curriculum for endodontic course had a significant impact on the quality of endodontic treatment performed by students.